Adaptação e validação de um questionário de barreiras de adesão à Terapia Antirretroviral para pessoas vivendo com HIV - Pereira, Míria Dantas (2024)
Although antiretroviral therapy (ART) for human immunodeficiency virus (HIV) has evolved significantly in recent decades, lack of treatment adherence remains a significant challenge to effective management of the condition. Several factors can impact adherence to ART, including socioeconomic barriers, treatment side effects, the relationship with the health system and the lack of social support. To address these obstacles, self-report questionnaires may be useful to assess the specific barriers faced by each patient. By identifying these barriers, it is possible to better understand individual adherence patterns and thus develop more effective strategies to improve ART adherence. The objective of this study was to adapt and validate the Adherence Barriers Questionnaire for HIV Patients on Antiretroviral Therapy (ABQ-HIV) for the Brazilian context, and to evaluate its psychometric properties in patients with HIV. A methodological study was carried out focused on analyzing the psychometric properties and factorial structure of the ABQ-HIV. The study consisted of seven sequential stages: (1) consent of the original authors; (2) translation by two translators; (3) synthesis of translations; (4) committee of expert judges; (5) back translation; (6) pre-test; and (7) assessment of reliability in the target population. The research was approved by the human research ethics committee (CAAE: 51176221.5.0000.5546). Participants were included between October 2022 and January 2023. In the evaluation carried out by a committee of experts, there was agreement between the 15 evaluating judges, resulting in a content validity index (CVI) of 0.93 for the items analyzed. 230 adult individuals living with HIV were included in the study. The median age (IQR) was 37.0 (29.3-45.0) and 120 were male (52.2%). The median time since diagnosis of HIV infection was 5.0 (IQR 2.0-9.0) years and the median duration of treatment since the start of ART was 5.0 (IQR 2.0-8.0) years. Exploratory Factor Analysis (EFA) was performed to evaluate the factorial structure of the ABQ-HIV. The Bartlett Sphericity test (1167.2 [136]; p < 0.001) and KMO = 0.602 suggested the interpretability of the item correlation matrix. The internal consistency of the scale was adequate (α = 0.76 and Ω = 0.76). Factor loadings varied between 0.32 (item 8) and 0.69 (item 11). The structure with three dimensions and 17 items showed good adjustment indicators: X2 = 89.931; degrees of freedom = 88; p > 0.005; RMSEA = 0.010; RMSR = 0.07; CFI = 0.996; GFI= 0.940; AGFI = 0.907; NNFI= 0.995. The ABQ-HIV demonstrated to be a valid and reliable instrument to identify specific barriers to adherence to ART in adults with HIV in the Brazilian population.